Comparative analysis of Staphylococcus aureus strains by molecular microbiology methods - Peles, Ferenc; Wagner, Martin; Keresztúri, Péter; Béri, Béla; Szabó, András (Acta Agraria Debreceniensis, 2007)
Staphylococcus aureus is a very important pathogen for dairy farms and milk processing plants. Subclinical mastitis is often caused by this species, and it can contaminate bulk tank milk when milking cows are suffering from mastitis. Additionally, thermostable enterotoxins (SE) produced by some types of this bacterium can cause food poisoning. The aim of our research was to examine the number of S. aureus in bulk tank milk in two dairy farms and the enterotoxin-producing ability, genetic relation (pulsotype) and antibiotic resistance of S. aureus strains from different sources (bulk tank milk, udder quarter milk and environment). The results show that the mean number of S. aureus of bulk tank milk of two farms significantly differed (P<0.05). Fourteen isolates were selected for further molecular genetic studies (five isolates were from bulk tank milk and nine isolates were from udder quarter milk). S. aureus was not recovered from the environmental samples. Three of the fourteen isolates (21.4%) tested by multiplex PCR were positive for SE genes. Two isolates carried one gene (seb) and one isolate carried two genes (seg and sei). The fourteen strains were classified into three pulsotypes and two subtypes at 86% similarity level. Isolates from bulk tank milk (n=5), were divided into 2 pulsotypes (A, C) and one subtype (C1). The isolates from udder quarter milk (n=9) belonged to three different pulsotypes (A, B, C) and two subtypes (A1, C1). The distribution of pulsotypes in the present study revealed genetic relationship between S. aureus isolated from udder quarter milk and bulk tank milk. This could be explained by the fact that in farms with a high number of infected cows, these cows could represent the main source of contamination. The results of the antibiotic resistance investigations show, that all strains were susceptible to methicillin, cefoxitin, lincomycin, tetracycline, erythromycin and sulfamethoxazole/trimethoprim. Thirteen out of fourteen strains were resistant to penicillin (A and C pulsotypes, A1 and C1 subtypes) and just one isolate was susceptible (B pulsotype) to all antibiotics tested.